2019
DOI: 10.1371/journal.ppat.1008192
|View full text |Cite
|
Sign up to set email alerts
|

A role of hypoxia-inducible factor 1 alpha in Murine Gammaherpesvirus 68 (MHV68) lytic replication and reactivation from latency

Abstract: Lytic replication of Kaposi's Sarcoma Associated Herpes Virus (KSHV) exacerbates Kaposi's sarcoma (KS) progression, an angiogenic spindle‐cell sarcoma associated with AIDS. Current antiviral therapy targeting lytic replication can prevent KS in seropositive patients. KSHV lytic infection is not manifested in vitro, and currently there are no animal models that display pathogenic phenotypes. In this study, we employed a biological and genetically mouse pathogen similar to KSHV, the murine gammaherpes virus (gHV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Hypoxia was found to be a powerful independent predictor of mortality in COVID-19 patients ( 33 ). Previous studies showed a strong relationship between hypoxia and both increasing the inflammatory response ( 34 ) and induction of viral replication ( 35 , 36 ). It might also play a role in the pathogenesis of hypercoagulation ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia was found to be a powerful independent predictor of mortality in COVID-19 patients ( 33 ). Previous studies showed a strong relationship between hypoxia and both increasing the inflammatory response ( 34 ) and induction of viral replication ( 35 , 36 ). It might also play a role in the pathogenesis of hypercoagulation ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several viruses, often associated with chronic infections, such as hepatitis C virus, herpesviruses, human papillomavirus and immunodeficiency virus (HIV), have been shown to induce HIF-1α activation, leading to metabolic cellular reprogramming and promotion of virus replication [ 31 , 34 , 35 ]. Influenza virus infection was also able to induce HIF-1α activation in lung carcinoma and monocytic cell lines; however, a lack of lung epithelial cell expression of HIF-1α in a mouse model of influenza infection was associated with enhanced virus replication [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later during lytic replication, the ORF34 lytic protein binds and stabilizes HIF-2α [45], which could promote eIF4E2-dependent translation [27]. Interestingly, HIF-1α is required for normal lytic gene expression during normoxia in both KSHV and murine gammaherpesvirus 68 infections [46,47]. In our experiments, the differential effects of eIF4E2 silencing on PEL proliferation suggests that KSHV latency does not fully recapitulate a hypoxic phenotype and suggests that KSHV selectively accesses the hypoxic gene expression program.…”
Section: Discussionmentioning
confidence: 72%